International environmental law - Naseem, Mohammad (Kluwer Law International, 2021)
Derived from the renowned multi-volume 'International Encyclopaedia of Laws', this book provides ready access to treaties, conventions, legislation and practice concerning the International Environmental Law. A general introduction covers geographic considerations, political, social and cultural aspects of environmental study, the history, sources and principles of environmental law, environmental legislation, carbon credits and the role of public authorities.00The main body of the book deals first with laws aimed directly at protecting the environment from pollution in specific areas such as air, water, waste, soil, noise, and radiation. Then, a section on nature and conservation management covers protection of natural and cultural resources such as monuments, landscapes, parks and reserves, wildlife, agriculture, forests, fish, subsoil, and minerals. Further treatment includes the application of zoning and land-use planning, rules on liability, and administrative and judicial remedies to environmental issues and disputes. There is also an analysis of the impact of international and regional legislation and treaties on environmental regulation.